Determinants of Housing Development in Nigeria - Mboto Helen Walter; Nkamare Stephen Ekpo; Edom Edom Onyam; Emefiele Charles Chike (Law and Economy, 2023)
The purpose of the study was to examine factors of mortgage that affect housing development in Nigeria. The specific objectives were to; examine the effect of interest rate, mortgage bank deposit, mortgage investment on housing development. Data for this study were sourced from secondary data and were extracted from the Central Bank of Nigeria (CBN) Statistical Bulletin and the National Bureau of Statistics, Nigeria. Data obtained were tabulated, analyzed and tested using the ordinary least square multiple regression statistical techniques. Based on the result, the findings revealed thus; there was a significant effect of mortgage loans on housing development; there was a significant effect of interest loans on housing development; there was a significant effect of mortgage investment on housing development, and there was a significant effect of mortgage bank deposit on housing development. The study recommended mortgage institutions should develop strategies to mobilize more deposits and ensure effective allocation of housing funds particularly for the low income earners. And finally government should create enabling environments to encourage private housing sector participation in long-term housing finance by providing infrastructure, enhancing soundness and competitiveness of mortgage institutions and assuring property rights.